Arylamine N-Acetyltransferase 1 Activity is Regulated by the Protein Acetylation Status - Salazar-González, Raúl A.; Doll, Mark A.; Hein, David W. (Frontiers in Pharmacology, 2022)
Arylamine N-acetyltransferase 1 (NAT1) is a drug metabolizing enzyme that influences cancer cell proliferation and survival, especially in breast cancer. Lysine-acetylation is an important Post-Translational Modification (PTM) in the regulation of diverse cellular processes. Histone deacetylases (HDACs) and Sirtuins (SIRT) may have an important role on the NAT1 acetylation status, affecting its catalytic capacity and having an impact on the downstream functions of this protein. The aim of the present work is to investigate the acetylation status of NAT1 in human breast cancer. Breast cancer cell lines MDA-MB-231 (ER-, PR-, HER2-) and ZR-75-1 (ER+, PR+, HER2+) were cultured in the presence of HDAC inhibitors (SAHA, TSA) or Sirtuin inhibitors (AGK2, EX527, Sirtinol). Under these conditions, NAT1 protein and gene expression as well as enzymatic activity were quantified. Acetylation of NAT1 protein was evaluated following an immunoprecipitation protocol and acetyl-Lysine quantification. Sirt1 and Sirt2 knockdown were performed and NAT1 protein and NAT1 mRNA expression and catalytic activity were quantified. The treatment of MDA-MB-231 or ZR-75-1 cells with increasing HDAC inhibitors resulted in 2 to 15-fold upregulation in NAT1 message expression. Finally, the catalytic activity of NAT1 in the presence of HDAC inhibition increased 2-fold. Conversely, the inhibition of Sirtuin activity did not cause significant changes in NAT1 message but produced a significant decrease in NAT1 catalytic activity. NAT1 acetylation was higher in in the cells treated with HDAC inhibitors, as well as Sirtuin inhibitors. Finally, silencing of Sirt1 and Sirt2 genes by siRNA transient knockdown of each or both genes resulted in reduction of NAT1 protein expression and catalytic activity. The use of HDAC and Sirtuin inhibitors has been demonstrated as a promising powerful therapeutic alternative in various cancers. These inhibitors can significantly attenuate tumor burden by limiting tumor growth and metastasis. These compounds can also induce DNA damage, cell cycle arrest, apoptosis, and autophagy to promote cancer cell death. Several studies have shown that NAT1 is upregulated in cancer cells. The results of the present study show that the acetylation status of NAT1 is an important factor that might have a relevant role in the progression of cancer.